Can Financial Strength Indicators Form A Profitable Investment Strategy? The Case Of F-Score in Europe - Andreas G. Koutoupis; Christos G. Kampouris; Athanasia V. Sakellaridou (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Can the F-Score predict the stock market returns in the cross section of international stock markets? Motivation - The majority of the literature, in the area of the F-Score metric, has examined whether it can be used to predict future financial profitability, the relationship of F-Score with book-to-value metrics and the momentum premium and whether it can be used as a successful investment strategy tool. There only three studies that examine the relationship between the F-Score and future stock returns, without the use of complementary variables, and in other countries except Europe. This paper seeks to fill this gap. Data - The dataset of the present research consists of listed European companies from 21 countries (in random order: Finland, United Kingdom, Switzerland, Turkey, Hungary, Portugal, Spain, Poland, Norway, Luxembourg, Italy, Netherlands, Ireland, Greece, Belgium Germany, Denmark, France Czech Republic, Sweden, Austria), from 1989 to 2016. We collect firm-level accounting information as provided by Worldscope, as well as the monthly total returns for common stocks from Datastream. Tools - With the use of a dataset consisting of European companies from 21 countries, portfolio analysis and time series regressions are performed using abnormal monthly returns (monthly returns minus risk-free interest rates). Findings - We find that the F-Score is a statistically significant predictor as well as an economically meaningful index. Its performance forecasting ability is visible in developed Europe, both in small and large companies, and remains stable after controlling for established cross-sectional determinants (such as book market, investment, and company size). Contribution - This study seeks to fill the gap in the stock return and F-Score relationship in a European setting controlling for the other financial variables. Our empirical models are tested across a number of different economic and stock market backgrounds and the implications of our results are of particular interest for academics, for investors (retail and institutional) and for policy makers.
Keywords: G11; G12; G15; M41; 650; F-Score; Stock Returns; Value Investing; Portfolio Analysis